2020
DOI: 10.1097/gox.0000000000002906
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Allergan’s Biocell Implant Recall in a Major University Breast Center

Abstract: Background: In May 2019, Health Canada released a national recall of all macrotextured breast implants that later became international in July 2019 regarding increasing accounts of suspected breast implant–associated anaplastic large cell lymphoma. In Canada, this recall targeted Allergan’s Biocell implants. This report presents the postmortem of this comprehensive single-center recall, which had to be undertaken in a limited time. Methods: Four months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Only 92 patients (5.9%) in their analysis requested implant explantation or removal with replacement. 11 When comparing studies from the United States to other countries, it is important to distinguish the vast differences in market penetration of textured implants between the United States and international markets. In Canada, textured implants at one point accounted for roughly 80% of the market share.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 92 patients (5.9%) in their analysis requested implant explantation or removal with replacement. 11 When comparing studies from the United States to other countries, it is important to distinguish the vast differences in market penetration of textured implants between the United States and international markets. In Canada, textured implants at one point accounted for roughly 80% of the market share.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have emerged discussing the management of textured implants and several provide data on their explantation/exchange rate, there are currently no data detailing the patient's perspective or reasoning for choosing removal of the textured devices versus monitored surveillance. [8][9][10][11][12] Given the paucity of literature examining the patient's decisions, the objective of this study was to identify patient actions in response to the FDA recall of the Style 410 anatomical textured implant.…”
mentioning
confidence: 99%
“…The United States FDA found that patients with textured Biocell implants (Allergan) were associated with an increasing number of BIA-ALCL, including an increase in mortality, prompting Allergan to a worldwide recall of their Biocell textured implants and tissue expanders in July of 2019. 5,22,110,111 The current recommendation is to remove this type of implant if a patient has BIA-ALCL, but not for asymptomatic patients.…”
Section: Recalled Implants Definitionmentioning
confidence: 99%
“…United States. 5,116 In patients with a history of breast reconstruction due to breast cancer, textured implants conferred an overall risk of developing BIA-ALCL as high as 1 in 355 women. 117…”
Section: Etiology and Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation